2022
DOI: 10.1111/ajo.13489
|View full text |Cite
|
Sign up to set email alerts
|

Views and practice of abortion among Queensland midwives and sexual health nurses

Abstract: Background: A significant barrier to the access of safe abortion is the lack of trained abortion providers. Recent studies show that with appropriate education, nurses and midwives can provide abortions as safely as medical practitioners.Aims: To examine the attitudes and practices of registered midwives (RMs) and sexual health nurses (SHNs) in Queensland toward abortion. Materials and Methods:A cross-sectional mixed-methods questionnaire was distributed to RMs and SHNs from the Queensland Nursing and Midwifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Given there is a scarcity of trained abortion care providers and that a skilled and safe workforce are central to delivering safe abortion care, we need to consider innovative models of delivery. In this edition of the Journal, Desai et al 13 INVITED EDITORIAL of a survey examining attitudes and practices of registered midwives (RMs) and sexual health nurses (SHNs) in Queensland toward abortion. The researchers found that although there was a wide variety of views, over half of participants would support abortion provision in any situation at all, and less than 8% were completely opposed to abortion due to their views and beliefs or conscience.…”
mentioning
confidence: 99%
“…Given there is a scarcity of trained abortion care providers and that a skilled and safe workforce are central to delivering safe abortion care, we need to consider innovative models of delivery. In this edition of the Journal, Desai et al 13 INVITED EDITORIAL of a survey examining attitudes and practices of registered midwives (RMs) and sexual health nurses (SHNs) in Queensland toward abortion. The researchers found that although there was a wide variety of views, over half of participants would support abortion provision in any situation at all, and less than 8% were completely opposed to abortion due to their views and beliefs or conscience.…”
mentioning
confidence: 99%